Legalidade tributária: conteúdo jurídico e requisitos - Silveira, Vítor Limeira Barreto da (2019)
The purpose of this Master's Dissertation is to know how tax law affects the laws that create or increase legal tax relationships that have as their object taxes of an eminently tax nature. Using Logical-semantic Constructivism as a method we seek to attribute a legal content to the species, as well as to point out the requirements that improve the legality in this scope of taxation. We emphasize legality as a form, legality as a collateral requirement (intrassistemic) and its relation to the rules of the same hierarchy and, in the end, legality as a semantic limitator (intranormative), pointing these as the requirements for the accomplishment of tax legality